2014
DOI: 10.1080/10875549.2014.951981
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness: Perception of Causes and Solutions

Abstract: This descriptive study investigated how working adult undergraduate students (N=115) view homelessness. Participants completed a survey assessing perceived causes, solutions, and stigma. Participants viewed poor economic conditions, limited availability of jobs, drug problems, and mental illness as leading causes of homelessness. Participants saw a variety of programs as potential solutions and denied that they would be socially distant from a formerly homeless person. Because responses were generally positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…In 2016, 116,427 people in Australia were homeless, representing 0.5 per cent of the population, and an increase of 14 per cent since 2012 (ABS, 2018). There are several definitions of homelessness, but the common aspect is being without a permanent home (Chamberlain and Johnson, 2001; Shinn, 2007; Phillips, 2014). A ‘home’ is not just a roof over one's head, but also a sense of privacy, safety, security, stability, and the ability to control the living space (Bonnefoy, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, 116,427 people in Australia were homeless, representing 0.5 per cent of the population, and an increase of 14 per cent since 2012 (ABS, 2018). There are several definitions of homelessness, but the common aspect is being without a permanent home (Chamberlain and Johnson, 2001; Shinn, 2007; Phillips, 2014). A ‘home’ is not just a roof over one's head, but also a sense of privacy, safety, security, stability, and the ability to control the living space (Bonnefoy, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies have discussed, people who are homeless may themselves consider their position to result from personal choices, whilst acknowledging that these choices were severely restricted. [48] Despite this, another study in the USA showed that around 57% respondents believed laziness to play a role in homelessness,[49] and it is likely that our results suggest that such negative perceptions of people who are homeless persist across Europe, with variances between countries.…”
Section: Discussionmentioning
confidence: 65%
“…Stereotypes of unhoused people as lazy, mentally ill, substance-abusing criminals are grounded in attributions for poverty and homelessness that emphasize personal responsibility and minimize structural sources of hardship (Bullock, Truong, & Chhun, 2017; Phelan, Link, Moore, & Stueve, 1997; Phillips, 2015). Unhoused women also contend with being stereotyped as “bad” mothers who are unable to materially provide for their children (Connolly, 2000a).…”
Section: Mothering While Homeless As a Violation Of The “Good Mother”mentioning
confidence: 99%